Pengaruh Konflik Kerja Dan Semangat Kerja Terhadap Kinerja Karyawan Divisi Avsec Angkasa Pura - Ilham Syuhada; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The purpose of this study was to determine the effect of work conflict and morale on employee performance in the Avsec Division of Angkasa Pura II Kuala Namu.The population in this study were employees of the Avsec Division of Angkasa Pura II Kuala Namu using a sample of 92 people. To obtain data in the preparation of this thesis, the author uses observation data collection instruments (observations), interviews, and distributes questionnaires. In analyzing the data using multiple linear regression, t test, f test, and determination test.The result showed that: (1) partially work conflict has an effect on employee performance in the avsec division of Angkasa Pura II Kuala Namu. (2) morale has an effect on employee performance in the Avsec division of Angkasa Pura II Kuala Namu. (3) Simultaneously work conflict and morale have an effect on employee performance in the Avsec division of Angkasa Pura II Kuala Namu.